Evaluation of a patient-centered communication skills training for nurses (KOMPAT): study protocol of a randomized controlled trial - Anja Lindig; Kendra Mielke; Wiebke Frerichs; Katja Cöllen; Levente Kriston; Martin Härter; Isabelle Scholl (BMC, 2024)
Abstract Background To ensure high quality of nurses' communication as part of patient-centered care, training of communication skills is essential. Previous studies indicate that communication skills trainings can improve communication skills of nurses and have a positive effect on emotional and psychological burden. However, most show methodological limitations, are not specifically developed for nurses or were developed for oncological setting only. Methods This study aims to evaluate the effectiveness of a needs-based communication skills training for nursing professionals and to derive indications for future implementation. A two-armed randomized controlled trial including components from both effectiveness and implementation research will be applied. Additionally, a comprehensive process evaluation will be carried out to derive indications for future implementation. Nurses (n=180) of a university medical center in Germany will be randomized to intervention or waitlist-control group. The intervention was developed based on the wishes and needs of nurses, previously assessed via interviews and focus groups. Outcomes to measure effectiveness were selected based on Kirkpatrick's four levels of training evaluation and will be assessed at baseline, post-training and at 4-weeks follow-up. Primary outcome will be nurses' self-reported self-efficacy regarding communication skills. Secondary outcomes include nurses' communication skills assessed via standardized patient assessment, knowledge about patient-centered communication, mental and work-related burden, and participants' satisfaction with training. Discussion To our knowledge, this is the first study systematically evaluating the effectiveness of a patient-centered communication skills training for nursing professionals in Germany. Results will yield insight whether a needs-based intervention can improve nurses' self-efficacy regarding communication skills and other secondary outcomes. Trial registration Clinical trial registration number: NCT05700929, trial register: ClinicalTrials.gov (date of registration: 16 November 2022).